Manfaat Dan Mafsadat Teknologi Modern Di Indonesia Perspektif Hukum Islam - Sakina; Kurniati; Marilang (An Nafi': Multidisciplinary Science, 2024)
Technology is an entity of objects and non-objects that is created in an integrated manner through human thoughts to achieve a value that can be utilized in human life. Modern technology has made it easier for humans to communicate even in different places. Islam is not an obstacle to technological development, but Islam is part of technological development. Islam plays a role in development today. Islam really appreciates technology, but Islam does not want humans to use technology in the wrong direction. The presence of technology in the perspective of Islamic law brings various benefits, namely as a means of approaching God, as an instrument for spreading Islamic law and as a solution to solving contemporary problems in the current era. Besides having benefits, technology also has benefits, namely distortion of religious information, ablation of traditional religious practices and social isolation.